Case report: A rare combination of aldosterone-secreting adrenocortical carcinoma and papillary thyroid carcinoma with Graves’ disease - Zhang, Yuhai; Yu, Jingwen; Fan, Cunxia; Wang, Fei; Liu, Haiwei; Chen, Kaining (Frontiers in Endocrinology, 2024)
Adrenocortical carcinoma (ACC) is a rare malignancy originating in the adrenal glands , aldosterone-producing ACC, even rarer. Papillary thyroid carcinoma (PTC) ,by contrast, accounts for the majority of thyroid carcinomas. We herein describe the first reported case of a female with comorbidities of aldosterone-producing ACC, PTC, and Graves' Disease(GD). The patient achieved transient clinical remission following adrenalectomy. However, three months later, aldosterone-producing ACC lung metastases emerged. Subsequently, within another three-month interval, she developed thyroid eye disease(TED). .The patient died roughly one year after the adrenal operation. Exome sequencing did not reveal associations between aldosterone-producing ACC, PTC, and GD, and the underlying concurrence mechanism has yet to be elucidated. Further research of similar cases are needed to confirm potential links between the three pathologies.